The Effect of Suitabillity of Product Description and Service Quality on Purchase Decisions on the Tokopedia Marketplace - Fika Narulita; Junaidi Gafar (Majalah Ilmiah Bijak, 2022)
This study aims to analyze the effect of suitability of product description and service quality on purchasing decisions on the Tokopedia marketplace. The population in this study are buyers who have bought products in the Tokedia marketplace with a minimum purchase of 1 time. Samples were taken from a representative samples (representing) with a total sample of 120. Data collection was done by distributing a list of questions or questionnaires to respondents to buyers who had bought products in the Tokopedia marketplace, about the suitability of product descriptions and service quality to purchasing decisions. This study uses instrument test analysis tools, classic assumption tests, simple linear regression analysis, multiple linear regression analysis and coefficient of determination test. The hypothesis is tested by t test and F test. The test results show tyhat the suitability of the product description partially influences but not significantly to the purchase decision, while the service quality partially has a significant effect on the purchase decision, and the suitability of the product description and service quality simultaneously has a significant effect on the decision purchase. The appropriateness of product description and service quality variables are able to explain the purchase decision variable by 29.4% and the remaining 70.6% is explained by other variables that are not thorough. and the suitability of the product description and service quality simultaneously has a significant effect on the decision purchase. The appropriateness of product description and service quality variables are able to explain the purchase decision variable by 29.4% and the remaining 70.6% is explained by other variables that are not thorough. and the suitability of the product description and service quality simultaneously has a significant effect on the decision purchase. The appropriateness of product description and service quality variables are able to explain the purchase decision variable by 29.4% and the remaining 70.6% is explained by other variables that are not thorough